(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information about the manuscript copies of Alauddin Samarkandi’s work “Sharh al-Ta’wilat”. Manuscript copies stored in library funds all over the world and their codicological classifications are revealed in it. In addition, the unique information found in the manuscripts of the work, the series of teachers of the Maturidi doctrine, the nasikhs and the information written in its margins are cited. The article also provides information such as the fact that this work was considered an authoritative commentary in the scientific circle in the 12th century in Mawarannahr, and that it was studied by foreign experts. It is noted that Alauddin Samarkandi himself read Maturidi’s work “Ta’wilat” together with Nasafi, he added comments to the places he found necessary, and later turned these comments into a separate book. In addition, it is highlighted that the work is a rare source in the direction of Hanafi tafsir.